Crowdsourcing as a new kind of employment relationship? (Research, Society and Development, 2021)
With the Covid-19 pandemic, unemployment increased exponentially, presenting crowdsourcing, that is, uberized work, as a way out for many unemployed workers. This paper aims to analyze in greater depth the process of uberization of individuals, proposing a discussion about the existence or not of the basic requirements for the configuration of the employment relationship, protected by Brazilian legislation, which guarantees the worker covered by this legal relationship their labor rights. For that, through jurisprudential and bibliographical research, it analyzes the process of uberization of the modern worker, especially in times of pandemic of Covid-19, to identify aspects/information that help to understand if uberization is configured as a job. Finally, it is concluded that with the advent of the Covid-19 pandemic, the number of informal workers who became uberized increased; the Brazilian judiciary has not yet established a peaceful position regarding the recognition of employment relationship; it is necessary to have its own legislative regulation, aiming to legalize the situation of these workers.